Membrane fouling in osmotically driven membrane processes: A review - She, Qianhong (2016)
The utilization of osmosis for engineered applications sparked off various emerging technologies relying on osmotically driven membrane processes (ODMPs). Represented by forward osmosis (FO) and pressure retarded osmosis (PRO), ODMPs show great promise to leverage the global water-energy nexus and have drawn considerable attention in recent years. However, their performance in practical applications is significantly affected by membrane fouling. Membrane fouling is a complex problem and is associated with the foulant deposition, concentration polarization and reverse solute diffusion (RSD) in ODMPs. The current paper provides a comprehensive review on membrane fouling in ODMPs with a focus on the elaboration of the factors and mechanisms governing the fouling behavior. Among those fouling factors and mechanisms, some are also applicable for pressure-driven membrane processes (e.g., reverse osmosis (RO) and nanofiltration (NF)), such as the effects of hydrodynamic conditions, feedwater composition, and membrane material and properties, and the cake-enhanced concentration polarization (CE-CP) mechanism. Others are unique for ODMPs, such as the effects of draw solution composition and membrane orientation, the internal concentration polarization (ICP) self-compensation effect, and the RSD-enhanced fouling. A general osmotic-resistance filtration model for ODMPs is presented in this paper to assist in the interpretation of the intrinsic interrelationships among those fouling factors and mechanisms. The impact and mechanisms of membrane fouling on contaminates removal are also reviewed briefly based on the limited existing literature on this topic. Finally, the available membrane fouling control strategies for ODMPs are summarized upon understanding the cause and effect of fouling. Based on the current review, future research prospects are proposed for further studying the membrane fouling in ODMPs.